2009
DOI: 10.1186/1617-9625-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of smoking quit attempts: Florida Tobacco Callback Survey, 2007

Abstract: ObjectiveThe public health burden of tobacco-associated diseases in the USA remains high, in part because many people's attempts to quit are unsuccessful. This study examined factors associated with having lifetime or recent attempts to quit smoking among current smokers, based on a telephone survey of Florida adults.MethodsData from the 2007 telephone-based Florida Behavioral Risk Factor Surveillance System (BRFSS) and its follow-up survey, the Tobacco Callback Survey, were used to assess determinants of havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…The results of a recent study corroborate this hypothesis, showing an association between having attempted to quit smoking and medical history of tobacco-related diseases. 6 The present study has strengths and limitations. The major strength is the coverage of our database, which includes data on 27 Brazilian cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a recent study corroborate this hypothesis, showing an association between having attempted to quit smoking and medical history of tobacco-related diseases. 6 The present study has strengths and limitations. The major strength is the coverage of our database, which includes data on 27 Brazilian cities.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,10,22,24 Risk of death shows a linear relationship with BMI. Individuals who are overweight are more likely to develop hypertension, type 2 diabetes, and risk factors for other chronic conditions such as dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Five reported that African Americans were significantly more likely than whites to have made a quit attempt. [18][19][20][21][22] Five other analyses reported nonsignificant differences between white and African American smokers in past-year quit attempts, [23][24][25][26][27] as did an analysis of nondaily smokers. 17 That publication 17 also reported that among daily smokers, whites were more likely than African Americans to have tried to quit for at least 1 day during the previous year.…”
Section: Quit Attempts During the Previous 12 Monthsmentioning
confidence: 99%
“…However, given that intention to quit smoking is shown to be one of the key steps in the process towards smoking cessation, it is important to study all quit attempts even those that are not successful. In order to adequately address all barriers to smoking cessation among these smokers and increase the proportion of successful quit attempts, it is important to understand the characteristics of smokers who have unsuccessfully tried to quit smoking (Davilla et al 2009).…”
Section: Introductionmentioning
confidence: 99%